Reading Goethe : a critical introduction to the literary work - Swales, Martin (Studies in German literature, linguistics, and culture., 2002)
The year 1999 saw the 250th anniversary of the birth of Johann Wolfgang von Goethe, Germany's greatest writer. Appropriately, literary scholars within Germany and beyond paid tribute to this remarkable talent. But a number of commentators also noted that.